Enzyme-free colorimetric determination of EV71 virus using a 3D-MnO2-PEG nanoflower and 4-MBA-MA-AgNPs. Issue 36 (30th August 2016) - Chu, Chengchao; Ge, Shengxiang; Zhang, Jing; Lin, Huirong; Liu, Gang; Chen, Xiaoyuan
Abstract : We present a simple colorimetric assay for EV71 virus detection based on the aggregation of 4-mercaptobenzoic acid (4-MBA) and melamine (MA) modified silver nanoparticles (4-MBA-MA-AgNPs) in the presence of Mn 2+ . Abstract : We present a simple colorimetric assay for EV71 virus detection based on the aggregation of 4-mercaptobenzoic acid (4-MBA) and melamine (MA) modified silver nanoparticles (4-MBA-MA-AgNPs) in the presence of Mn 2+ . The EV71-Ab1 was incubated on a 96-well plate and the EV71-Ab2 was labeled on the surface of three-dimensional nanoflower-like MnO2 -PEG (3D-MnO2 -PEG). After layer-by-layer immunoreactions, the EV71 virus and the corresponding 3D-MnO2 -PEG-Ab2 were captured on the plate. With the addition of Vitamin C (Vc), Mn 2+ was released from the 3D-MnO2 -PEG and then the aggregation of the 4-MBA-MA-AgNPs was induced, allowing a naked-eye detection limit of EV71 virus to be as low as 5 × 10 4 particles per mL, which is about three orders of magnitude lower than the conventional enzyme-linked immunosorbent assay (ELISA). This enzyme-free immunoassay based on a hybrid 3D-MnO2 features signal amplification strategies via a simple reduction reaction.